The Influence of School Image, Service Quality, and Parental Trust on School Choice Decisions - Wernando Wilys Aritonang; Ronald Suryaputra; Dany M. Handarini (Journal of Educational Management Research, 2026)
The increasing competition among private educational institutions has heightened the need for effective educational management strategies to understand factors influencing parents’ school choice decisions. This study aims to analyze the influence of school image, educational service quality, and parental trust on parents’ decisions to choose Northern Green School Medan. The study is motivated by a noticeable decline in student enrollment in recent years, which reflects weakening parental preference amid intensified competition among private schools. Employing a quantitative research design, data were collected through a survey administered to parents of enrolled students and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that school image and educational service quality have a positive and significant effect on parents’ school choice decisions. Furthermore, parental trust emerges as the most dominant factor influencing parents’ decisions among the examined variables. The structural model demonstrates strong explanatory power, with an R² value of 0.843, indicating that 84.3% of the variance in parents’ school choice decisions is explained by the proposed model. These findings imply that private schools need to prioritize trust-based management practices, consistently improve the quality of educational services, and strengthen institutional image to enhance parental confidence and sustain student enrollment in a competitive educational environment.